Oligomers of poly(anhydride): Study of interaction in coating binder - Lasne-Deschamps, Anne-Cécile; Faÿ, Fabienne; Sire, Olivier; Linossier, Isabelle; Vallée-Réhel, Karine (Journal of applied polymer science, 2012)
Polyanhydrides are largely used in biomedical and pharmaceutical fields because of their biodegradability and controlled degradation. In this work, oligomers were investigated as film binders for environmental applications. To overcome the main disadvantages of polyanhydrides (low solubility in common solvents and high melting points), oligomers based on sebacic acid were prepared. Characterization was carried out by nuclear magnetic resonance and electrospray ionization to obtain chemical structures of the products. The formation of weak interactions, which confer cohesion between chains, allows film properties to be observed. The impact of the solvent polarity on the specific organization was investigated by a combination of focused methods: capillary viscosimetry, IR spectroscopy, polarized light microscopy, and X‐ray diffraction. © 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012